Association of the c.75C>A Variant in CLCC1 with Autosomal Recessive Retinitis Pigmentosa in Pakistan - Waryah, Yar Mohammad; Feriha Fatima Khidri; Amir Ansari; Samia Mehmood; Sumera Abbasi; Shabahat Memon (Journal of Liaquat University of Medical & Health Sciences, 2024)
Objective: To identify the disease-causing allele of retinitis pigmentosa, a heterogeneous genetic disorder in a single affected family. Methodology: A cross-sectional descriptive study was conducted at the Sindh Institute of Ophthalmology & Visual Sciences Hyderabad from December 2022 to December 2023, with approval from the SIOVS ethical committee. A consanguineous pedigree with multiple affected members was included, while pedigrees with only one affected member or secondary causes of vision loss were excluded. After getting informed consent, each enrolled participant’s blood samples (10 cc) were collected, and DNA was extracted. The family was subjected to Sanger sequencing for the CLCC1 gene. Results: In this study, one reported c.C75A, p.Asp25Glu allele in the CLCC1 gene was identified from an endogamous pedigree in Sindh, Pakistan. The identified c.C75A, p.Asp25Glu allele is a common cause of autosomal recessive retinitis pigmentosa (arRP) in Pakistani-affected individuals. This allele is estimated to have occurred 2000-5000 years ago and has been transmitted to affected individuals of Pakistani origin and global descent across various geographical regions. All the affected patients underwent detailed clinical investigations, including fundus photography and optical coherence tomography, to confirm the retinitis pigmentosa symptoms. The Sanger sequencing method was used to detect pathogenic variants, and bioinformatics tools were utilized to investigate the pathogenesis of identified alleles and compare phenotype-genotype correlations. Conclusion: The finding of frequent disease-causing alleles from Pakistani-affected patients will significantly improve existing genetic databases and facilitate more accurately the affected diagnosis of gene testing.